PERGURUAN TINGGI ISLAM DAN TRANSFORMASI LEMBAGA: STUDI TERHADAP PROSES PERUBAHAN FUNGSI DAN PERAN IAIN SYARIF HIDAYATULLAH JAKARTA MENJADI UNIVERSITAS ISLAM - Sari, Ramadhanita Mustika (El -Hekam, 2016)
The transformation has been carried out by IAIN Syarif Hidayatullah State Islamic University Jakarta be led to changes in this educational institution. It was seen on the graduates produced. Whereas in the past, Islamic Religious Institutions spawned a cadre (personnel scholars) who are experts in the field of Islamic Theology, Syariah, Tarbiyah, Da’wah and Adab. However, after becoming the Islamic University, the scholar who produced not only Muslim scholars, but also can be moslem doctor, moslem economists, moslem psychologists. Changes of IAIN Syarif Hidayatullah inti State Islamic University Jakarta become an impact on changes in the function and role of this College. UIN Syarif Hidayatullah Jakarta contribute to sustainable development (sustainable development), and the development of society as a whole. In that context, the mission and function more specifically, namely: First, the curriculum applied at UIN Syarif Hidayatullah Jakarta aims to educate students to meet the needs of all sectors of human activity, by offering relevant qualifications, including education and professional training which combines science and high-level expertise through courses continue to be designed, evaluated regularly, and continue to be developed to address the various needs of the people present and the future. Second, UIN Syarif Hidayatullah Jakarta strives to promote, create and disseminate knowledge through research; and develop research in the field of science and technology, social sciences, humanities and creative arts. Third, UIN Syarif Hidayatullah Jakarta also has a vision to help understand, interpret, preserve, strengthen, develop, and disseminate historical cultures of national, regional and international levels in pluralism and cultural diversity in the community.Keywords: Islamic University, Institutional Transformation, UIN Syarif Hidayatullah Jakarta